3D printed microelectronics & new design thinking (Transactions on Additive Manufacturing Meets Medicine, 2023)
The need for more complex but sustainable electronics makes electronic development an increasingly convoluted task. New manufacturing tools and methods are thereby required to generate new sustainable proposals without resigning on complexity such as Additive Manufacturing of Electronics (AME). Additive manufacturing of printed electronics is replacing traditional development processes in new ways by enabling complex geometries, embedding 3D-printed components and significantly shortening the development cycle. Furthermore, AME enables embedding of passive and active components within a single package/board. Nano Dimension uses a manufacturing process (inkjet printing) in which conductive silver nanoparticle ink and insulating ink are bonded and cured/sintered layer by layer, allowing new geometric freedom in 3D and thus a variety of novel applications (RF, IC staking, encapsulated sensors, unconventional system-in-package solutions) allowing them to include complex features such as curved vias, coaxial and waveguide transmission lines or truly twisted pair routings. This presentation will showcase the latest developments of AME technology within Nano Dimension and how Nano Dimension foresees the future design of printed circuit boards, starting with the status quo on current PCB technologies, the generalities of the AME process, and the AME potential applying a new design thinking for RF applications, multilayer and complex high density interconnects (HDI, non-planar transmission lines, embedding & encapsulation of components, and electromechanical printed devices, finishing with ways to achieve it using current 2D ECAD tools along with 3D MCAD.
Keywords: Additive Manufacturing of Electronics; AME